Epidemiology of amyotrophic lateral sclerosis in Emilia Romagna Region (Italy): A population based study. Issue 3 (June 2014) - Mandrioli, Jessica; Biguzzi, Sara; Guidi, Carlo; Venturini, Elisabetta; Sette, Elisabetta; Terlizzi, Emilio; Ravasio, Alessandro; Casmiro, Mario; Salvi, Fabrizio; Liguori, Rocco; Rizzi, Romana; Pietrini, Vladimiro; et al.
Abstract: Our objective was to describe incidence and clinical features of ALS from a prospective population-based study in Emilia Romagna Region (ERR). From 2009 onwards, a prospective registry recorded all incident cases of ALS among residents in the ERR (population, 4.4 million inhabitants), involving 17 neurological departments. For each patient, detailed demographic and clinical information was collected by caring physicians. Results showed that from 1 January 2009 to 31 December 2011, 347 patients received a new diagnosis of ALS with a crude incidence rate of 2.63/100, 000/year. There was micro-geographic heterogeneity throughout ERR, with higher incidence rates in the low density population (3.27/100, 000) ( p < 0.01). ALS patients have been more frequently employed in agriculture than the general ERR population (8.64% vs. 4.6%, p < 0.01). Clinical features were similar to those described in previous population based studies. In conclusion, we report incidence rates similar to those reported by European registries, reflecting good accuracy of our prospective study. We confirmed previous studies reporting higher incidence rates in rural areas and among agricultural workers. Although genetics has been gaining increasing importance in ALS aetiology, some epidemiological data are still unexplained. Identifying geographical areas or populations with high incidence rates can be a starting point for identifying environmental risk factors. Further studies having this specific aim can shed light on these topics.